Analysis of Critical Thinking Ability of Elementary School Students in Learning Mathematics with Problem-Based Learning Model - Sari, Melinda Tri Buana Puspita; Wahyudin (International Conference on Elementary Education, 2025)
This research aims to describe the mathematical critical thinking abilities of elementary school (SD) students in mathematics learning using the Problem-Based Learning model and to determine the indicators of critical thinking abilities that students master best. This research was carried out in order to determine the abilities of students who have critical thinking skills who are expected to have a scientific attitude, good problem solving abilities in learning and in everyday life. The research method used is descriptive qualitative. This research was conducted at SDN Bandung Elementary School by taking a sample of 4 students. The instruments used in this research are instruments about critical mathematical thinking skills and interview instruments. The data collection method begins with learning observations, then students are asked to work on critical mathematical thinking skills questions through Problem-Based Learning, then interviews are conducted with students and class teachers. The research results show that the Problem Based Learning learning model used can hone students’ critical thinking skills, based on indicators that have been determined, 3 students have various critical thinking abilities.